Auditoría energética de la Facultad de la Energía, las Industrias y de los Recursos Naturales no Renovables de la Universidad Nacional de Loja, con propuesta de red inteligente para la gestión eléctrica. - Conde Jiménez, Ronier Francisco (2022)
The present research work evaluates the operating conditions of the electrical system of the Faculty of Energy, Industries and Non-Renewable Natural Resources (FEIRNNR), of the National University of Loja, developing an audit of its electrical system, allowing the generation of inventories of energy-consuming elements and identify their operating conditions, to establish points of failure of the electrical network and develop proposals that allow reducing electricity consumption, thus improving the efficiency of energy use and generating reduction in billing costs. For this an analysis of the electrical consumption records retrieved from the database of the Empresa Eléctrica Regional del Sur S.A. was developed. (EERSSA) information that allowed the understanding of the dynamics of operation of the electrical network of the Faculty to establish its behavior in conditions of maximum and minimum consumption, which complemented with a process of analysis and identification of the different elements that structure the electrical network of the faculty, allows to establish points of improvement to the network. Once the possible points of failure in the electrical network and energy consuming elements have been determined, the necessary recommendations are established to correct or replace the elements that cause instability, using energy management standards and norms as a guide, establishing the necessary changes according to the information collected in the inventories and tests carried out, thus raising the need to migrate from lighting source technology in the different areas of the Faculty, which allows generating management policies and better management of the electrical network. Thus establishing guidelines for future resource optimization work in the different faculties of the National University of Loja, incorporating new technologies to the management of the electrical network that enable the incorporation of alternative energy generation sources. Keywords: Energy Efficiency, Energy, NEC, ISO, IEEE.